Information systems in family agriculture: monitoring the use of software for financial management of properties / Sistemas de informação na agricultura familiar: acompanhamento do uso de software para gestão financeira das propriedades / Sistemas de información en la agricultura familiar: seguimiento del uso de software para la gestión financiera de propriedades - Aguiar, Evandro Mendes de; Lago, Sandra Mara Stocker; Ito, Giani Carla; Bertolini, Geysler Rogis Flor (REVISTA NERA, 2023)
This article aimed to analyze the monitoring of the use of financial management software by family farmers. Data on the use of the software were collected and tabulated from ten producers in the west and northwest region of Paraná, in addition to conducting a semi-structured interview with a field professional from a service cooperative. During the interview, it was identified that the producers’ knowledge about finance is basic and superficial. However, even with limited knowledge, producers use the practice of a handwritten cash flow. Finally, it was concluded that the producers lack training and technical depth in the financial management of the property, uncomplicated tools, and that have their operation on mobile devices, however, they demonstrate conditions to use basic controls such as cash flow. It also revealed that producers are not available to acquire information technology resources because they do not have the financial resources to acquire them